PRODUCTIVITY COMPARISON BETWEEN BOER AND KACANG GOAT DAM - Elieser, S.; Sumadi, S.; Budisatria, G.S.; Subandriyo, S. (Diponegoro University, 2012)
A study to evaluate the productivity of Boer and Kacang goats dam was carried out for 2 years atResearch Institute for Goat Production, Sungei Putih-North Sumatera. The materials used were goatsowned by the institute. The parameters observed were total birth and weaning weights of kid, litter size,parity of dam, pre-weaning mortality and kidding interval. The rate of reproduction and productivity ofthe dam were estimated using Amir and Knipscheer methods and were statistically analyzed usingGeneral Linear Model. The results showed that the total birth and weaning weight of Boer goats werehigher (P<0.05) than that of Kacang goats, while litter size of Boer goats were higher (P<0.05) than thatof Kacang goats. The pre-weaning mortality of Boer goat 15.1 ± 6.02% was lower than that ofKacang. The kidding interval of Boer goats was higher (P<0.05) than that of Kacang. Parity of dam hadsignificant effect on all production traits (P<0.05) except for pre-weaning mortality. Dam reproductionrate of Boer (1.81) was higher than that of Kacang (1.78), while productivity of Boer goat (37.12kg/head/year) was higher than that of Kacang (18.12). It can be concluded that the reproductivity ofBoer and Kacang goats were similar, however the productivity of Boer goat had better than Kacang.